Development of a complex Interdisciplinary Nurse-coordinated SELf-MAnagement (INSELMA) intervention for patients with inflammatory arthritis - Jette Primdahl; Ann Bremander; Oliver Hendricks; Mikkel Østergaard; Kristine Marie Latocha; Lena Andersen; Kim Vilbaek Jensen; Bente Appel Esbensen (BMC Health Services Research, 2024)
Abstract Background Apart from a consistent focus on treating inflammation, patients with inflammatory arthritis (IA) report a range of unmet needs. Many experience not only residual symptoms but also various other physical, psychological, and social effects. Therefore, this study aimed to develop a complex Interdisciplinary Nurse-coordinated self-management (INSELMA) intervention for patients with IA, as an add-on treatment to usual outpatient care for those with substantial disease impact. Methods This study followed the British Medical Research Council’s updated framework for developing complex interventions. The process encompassed the following steps: (1) The evidence base was identified; (2) workshops were held, involving 38 relevant stakeholders (managers, physicians, nurses, physiotherapists, occupational therapists, social workers, psychologists from hospitals and municipalities, and two patient research partners), to discuss and further develop the preliminary ideas; (3) relevant theories were identified (i.e., self-efficacy, acceptance and commitment therapy, and health literacy); (4) the intervention was modeled and remodeled and (5) the results, describing the final INSELMA intervention and outcomes. Results The INSELMA intervention encompasses an initial biopsychosocial assessment, which is performed by a rheumatology nurse. Then, activities that the participant wishes to improve are identified and goals are set. The nurse refers the participant to a multidisciplinary team and coordinates their support and relevant services in the participant’s municipality. In addition, the health professionals have the opportunity to hold two interdisciplinary conferences during the intervention period. The participant and the health professionals work to achieve the set goals during a 6-month period, which ends with a status assessment and a discussion of further needs. The INSELMA intervention aims to increase self-management, reduce the impact of IA (e.g., pain, fatigue, sleep problems, and absenteeism), and increase self-efficacy, quality of life, mental well-being, work ability, and physical activity. Conclusions The development of the INSELMA intervention involved stakeholders from two Danish rheumatology outpatient clinics, patient research partners and municipalities. We believe that we have identified important mechanisms to increase the self-management and quality of life of people with IA and to decrease the disease impact in those who are substantially affected. The health professionals involved have developed competences in delivering the intervention and it is ready to be tested in a feasibility study.